2016
DOI: 10.1002/2016jb012821
|View full text |Cite
|
Sign up to set email alerts
|

Geomechanical analysis of fluid injection and seismic fault slip for theMw4.8 Timpson, Texas, earthquake sequence

Abstract: An earthquake sequence that culminated in a Mw4.8 strike‐slip event near Timpson, east Texas, the largest reported earthquake to date in that region, had previously been attributed to wastewater injection starting 17 months before the onset of recorded seismic activity. To test if this earthquake sequence can be attributed to wastewater injection, we conducted coupled poroelastic finite element simulations to assess the spatial and temporal evolution of pore pressure and stress field in the vicinity of the inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 57 publications
1
65
0
Order By: Relevance
“…A search of records at station NATX in Nacogdoches (about 35 km distant) revealed that several small earthquakes, apparently from the same focus, had occurred in 2008, 2010, and 2011 (Frohlich et al, 2014), and subsequent reanalysis of Transportable Array data revealed additional earthquakes that occurred between 2010 and 2012 (Walter et al, 2016). Fan et al (2016) simulated the spatial and temporal evolution of the pore pressure and stress fields in this region using a coupled finite-element geomechan-▴ Figure 11. Earthquakes, injection wells, and production wells at the Dallas-Fort Worth (DFW) International Airport.…”
Section: Cleburne 2009-2012: Almost Certainly Inducedmentioning
confidence: 99%
“…A search of records at station NATX in Nacogdoches (about 35 km distant) revealed that several small earthquakes, apparently from the same focus, had occurred in 2008, 2010, and 2011 (Frohlich et al, 2014), and subsequent reanalysis of Transportable Array data revealed additional earthquakes that occurred between 2010 and 2012 (Walter et al, 2016). Fan et al (2016) simulated the spatial and temporal evolution of the pore pressure and stress fields in this region using a coupled finite-element geomechan-▴ Figure 11. Earthquakes, injection wells, and production wells at the Dallas-Fort Worth (DFW) International Airport.…”
Section: Cleburne 2009-2012: Almost Certainly Inducedmentioning
confidence: 99%
“…In addition, both moment tensors were subsequently recalculated on 23 June 2016 using a more refined local velocity model [see Herrmann, 2016], resulting in two strike-slip focal mechanisms with similar nodal plane and P axis orientations to one another (Figure 2d). Fan et al [2016] demonstrate that poroelastic stress changes could allow P P to build to the point that a severely misoriented fault could slip, but a requirement of their model is that no well-oriented faults are present. At the~2.5 km top-fault depth shown by Frohlich et al [2014], only 1.8-6.8 MPa ΔP P in the case of the 17 June 2012 M w 4.8 earthquake and 0.7-2.7 MPa ΔP P for the 10 June 2012 M w 3.8 earthquake were needed to trigger slip (Table 1).…”
Section: Implications For Faulting Associated With Seismicitymentioning
confidence: 99%
“…Most studies addressing the correlation between injection and nearby seismicity either are qualitative (Ake et al, 2005;Frohlich, 2012) or quantify pore pressure using uncoupled groundwater flow equations Keranen et al, 2014). Recent studies consider coupling between pore pressure and matrix deformation to investigate the relationship between injection and earthquakes (Deng et al, 2016;Fan et al, 2016;Segall & Lu, 2015;Shirzaei et al, 2016). This relationship is a function of injection rate, local hydrogeology, initial pore pressure and background stress state, fault orientation and permeability, and frictional properties (Chang & Segall, 2016;Fan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%